P662 Remission to vedolizumab is not higher in TNF-naïve compared with TNF-pre-treated patients with Crohn's disease. (25th January 2019) - Biedermann, L; Mader, O; Hruz, P; Juillerat, P; Michetti, P; Pittet, V; Rogler, G; Seibold, F
Abstract: Background: Vedolizumab (VDZ) a humanised monoclonal antibody against α4β7 integrin is used in Crohn's disease (CD) and ulcerative colitis (UC). It is still unclear whether biologic-naive patients will respond better to VDZ than TNF-pre-treated patients in a real life setting. Our study aimed to determine the efficacy of VDZ among TNF-pre-treated compared with TNF-naive patients. Methods: In total, 265 patients of the Swiss IBD cohort study were analysed, 17 patients were excluded due to incomplete data. Of the remaining 248 patients 130 suffered from CD and 118 patients from UC. Remission was defined as calprotectin < 200 mg/kg in faecal samples and/or mucosal healing determined by endoscopy. Endpoints were determined between month 4 and 8 and between month 12 and 16 after VDZ induction. Results: In total, 112 patients (45%) (43% CD and 48% UC) achieved remission between month 4 and 8 and 130 patients (52%) at month 12 and 16. In patients with UC, significantly more TNF-naïve patients (60%) achieved remission compared with TNF-pre-treated patients (33%) ( p = 0.01, OR 0.24, CI 0.09–0.65). In patients with CD however, we observed no significant difference between TNF-pre-treated and TNF-naive patients. Almost a third of all patients discontinued VDZ treatment (29.8%), the most frequent reason was non-response to VDZ (20%), followed by adverse events (6%) and exacerbation of extraintestinal manifestations (3%). Conclusions: A significant proportion of patients TNF-naïve and TNF-pre-treated patients achieved remission. Previous anti-TNF failure was associated with a lower efficacy of VDZ in UC patients between month 4 and 8, whereas remission rates in anti-TNF–naïve vs. experienced CD patients were similar.